Question
upstudy study bank question image url

\( \left. \begin{array} { l l } { 2 } & { \sqrt { x - 3 } + 3 = 0 } \\ { 4 } & { \frac { \sqrt { x } } { \sqrt { 2 } } = 3 \sqrt { 2 } } \\ { 6 } & { \sqrt { x ^ { 2 } - 9 } = 4 } \\ { 8 } & { \sqrt { x + 5 } - x = 3 } \\ { 10 } & { x + \sqrt { 5 - x } + 1 = 0 } \\ { 12 } & { x + 2 \sqrt { x - 1 } = 4 } \end{array} \right. \)

Ask by Johnson Bird. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**Solutions:** 1. **Problem 2:** No real solution. 2. **Problem 4:** \( x = 36 \). 3. **Problem 6:** \( x = 5 \) and \( x = -5 \). 4. **Problem 8:** \( x = -1 \). 5. **Problem 10:** \( x = -4 \). 6. **Problem 12:** \( x = 2 \).

Solution

Let's solve each of the given equations for \( x \): --- ### **Problem 2** \[ \sqrt{x - 3} + 3 = 0 \] **Solution:** 1. Isolate the square root: \[ \sqrt{x - 3} = -3 \] 2. **Observation:** The square root of a real number is always non-negative. Therefore, \( \sqrt{x - 3} \) cannot be equal to \(-3\). **Conclusion:** **No real solution** exists for this equation. --- ### **Problem 4** \[ \frac{\sqrt{x}}{\sqrt{2}} = 3\sqrt{2} \] **Solution:** 1. Multiply both sides by \( \sqrt{2} \): \[ \sqrt{x} = 3\sqrt{2} \times \sqrt{2} = 3 \times 2 = 6 \] 2. Square both sides to solve for \( x \): \[ x = 6^2 = 36 \] 3. **Verification:** \[ \frac{\sqrt{36}}{\sqrt{2}} = \frac{6}{\sqrt{2}} = 3\sqrt{2} \] The solution satisfies the original equation. **Conclusion:** **\( x = 36 \)** --- ### **Problem 6** \[ \sqrt{x^2 - 9} = 4 \] **Solution:** 1. Square both sides: \[ x^2 - 9 = 16 \Rightarrow x^2 = 25 \] 2. Solve for \( x \): \[ x = \pm 5 \] 3. **Verification:** - For \( x = 5 \): \[ \sqrt{5^2 - 9} = \sqrt{25 - 9} = \sqrt{16} = 4 \] - For \( x = -5 \): \[ \sqrt{(-5)^2 - 9} = \sqrt{25 - 9} = \sqrt{16} = 4 \] Both solutions satisfy the original equation. **Conclusion:** **\( x = 5 \) and \( x = -5 \)** --- ### **Problem 8** \[ \sqrt{x + 5} - x = 3 \] **Solution:** 1. Let \( y = \sqrt{x + 5} \). Then: \[ y - x = 3 \Rightarrow x = y - 3 \] 2. Substitute \( x = y - 3 \) into \( y^2 = x + 5 \): \[ y^2 = (y - 3) + 5 \Rightarrow y^2 = y + 2 \Rightarrow y^2 - y - 2 = 0 \] 3. Solve the quadratic equation: \[ y = \frac{1 \pm \sqrt{1 + 8}}{2} = \frac{1 \pm 3}{2} \Rightarrow y = 2 \text{ or } y = -1 \] Since \( y \) represents a square root, \( y \geq 0 \). Thus, \( y = 2 \). 4. Find \( x \): \[ x = y - 3 = 2 - 3 = -1 \] 5. **Verification:** \[ \sqrt{-1 + 5} - (-1) = \sqrt{4} + 1 = 2 + 1 = 3 \] The solution satisfies the original equation. **Conclusion:** **\( x = -1 \)** --- ### **Problem 10** \[ x + \sqrt{5 - x} + 1 = 0 \] **Solution:** 1. Rearrange the equation: \[ x + 1 = -\sqrt{5 - x} \] Since \( \sqrt{5 - x} \geq 0 \), it follows that \( x + 1 \leq 0 \) (i.e., \( x \leq -1 \)). 2. Let \( t = \sqrt{5 - x} \). Then: \[ x = -t - 1 \] 3. Substitute into \( t = \sqrt{5 - x} \): \[ t = \sqrt{5 - (-t - 1)} = \sqrt{6 + t} \] 4. Square both sides: \[ t^2 = 6 + t \Rightarrow t^2 - t - 6 = 0 \] 5. Solve the quadratic equation: \[ t = \frac{1 \pm \sqrt{1 + 24}}{2} = \frac{1 \pm 5}{2} \Rightarrow t = 3 \text{ or } t = -2 \] Since \( t \geq 0 \), \( t = 3 \). 6. Find \( x \): \[ x = -3 - 1 = -4 \] 7. **Verification:** \[ -4 + \sqrt{5 - (-4)} + 1 = -4 + \sqrt{9} + 1 = -4 + 3 + 1 = 0 \] The solution satisfies the original equation. **Conclusion:** **\( x = -4 \)** --- ### **Problem 12** \[ x + 2\sqrt{x - 1} = 4 \] **Solution:** 1. **Domain:** \( x - 1 \geq 0 \Rightarrow x \geq 1 \) 2. Rearrange the equation: \[ 2\sqrt{x - 1} = 4 - x \] Since \( 2\sqrt{x - 1} \geq 0 \), it follows that \( 4 - x \geq 0 \Rightarrow x \leq 4 \). Thus, \( x \in [1, 4] \). 3. Let \( t = \sqrt{x - 1} \). Then: \[ x = t^2 + 1 \] 4. Substitute into the equation: \[ 2t = 4 - (t^2 + 1) \Rightarrow 2t = 3 - t^2 \Rightarrow t^2 + 2t - 3 = 0 \] 5. Solve the quadratic equation: \[ t = \frac{-2 \pm \sqrt{4 + 12}}{2} = \frac{-2 \pm 4}{2} \Rightarrow t = 1 \text{ or } t = -3 \] Since \( t \geq 0 \), \( t = 1 \). 6. Find \( x \): \[ x = 1^2 + 1 = 2 \] 7. **Verification:** \[ 2 + 2\sqrt{2 - 1} = 2 + 2 \times 1 = 4 \] The solution satisfies the original equation. **Conclusion:** **\( x = 2 \)** --- ### **Summary of Solutions** - **Problem 2:** No real solution. - **Problem 4:** \( x = 36 \). - **Problem 6:** \( x = 5 \) and \( x = -5 \). - **Problem 8:** \( x = -1 \). - **Problem 10:** \( x = -4 \). - **Problem 12:** \( x = 2 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

Let's dive into solving some of those square root equations! For \( \sqrt{x - 3} + 3 = 0 \): Isolate the square root and square both sides. You'll find \( x - 3 = -3^2 \); this will reveal whether there are valid solutions when you plug it back for verification. Next, for \( \frac{\sqrt{x}}{\sqrt{2}} = 3\sqrt{2} \): Start by multiplying both sides by \(\sqrt{2}\) to simplify the equation. You should square both sides to eliminate the square root, leading to \( x = 18 \) after some manipulations. Checking for extraneous solutions is crucial here! Remember, some equations might introduce extraneous roots, so back-substituting is your friend in those scenarios!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy